Pengaruh Promosi dan Brand Image terhadap Keputusan Pembelian Smartphone - Renouw, Ade Andriani; Maryen, Andrei; Renhoar, Teli Desna (Innovative: Journal Of Social Science Research, 2024)
The purpose of this study was to analyze the influence of promotion and brand image on purchasing decisions for Samsung smartphones at Pink Cellular, Sorong City. The data testing strategy used was quantitative graphic analysis. Testing with the Slovin equation was carried out on 76 respondents. The results of the t-test, the independent variable partially, the t value of the promotion has a significant effect on the dependent variable, where the t value of the promotion variable is tcount 7.521> ttable 1.6716 or the significance value of t-table 0.000, it can be concluded that the hypothesis (H1) is accepted, the brand image variable is tcount 3.712> ttable 1.6716 or the significance value of t-table 0.000, it can be concluded that the hypothesis (H2) is accepted. The results of the F test obtained an F value of 41.088 with a significance of 0.000. it appears that the importance value <0.05. implies that progress and brand image simultaneously influence the choice of purchasing Samsung Smartphones at Pink Cellular in Sorong City.